Clinical features and outcomes of patients with malignancy and Takotsubo syndrome: observations from the International Takotsubo Registry - Cammann, Victoria Lucia; Sarcon, Annahita; Ding, Katharina J.; Seifert, Burkhardt; Kato, Ken; Di Vece, Davide; Szawan, Konrad A.; Gili, Sebastiano; Jurisic, Stjepan; Bacchi, Beatrice; Micek, Jozef; Frangieh, Antonio H.; et al. (Journal of the American Heart Association, 2019)
Background: Clinical characteristics and outcomes of takotsubo syndrome (TTS) patients with malignancy have not been fully elucidated. This study sought to explore differences in clinical characteristics and to investigate short‐ and long‐term outcomes in TTS patients with or without malignancy. Methods and Results: TTS patients were enrolled from the International Takotsubo Registry. The TTS cohort was divided into patients with and without malignancy to investigate differences in clinical characteristics and to assess short‐ and long‐term mortality. A subanalysis was performed comparing long‐term mortality between a subset of TTS patients with or without malignancy and acute coronary syndrome (ACS) patients with or without malignancy. Malignancy was observed in 16.6% of 1604 TTS patients. Patients with malignancy were older and more likely to have physical triggers, but less likely to have emotional triggers compared with those without malignancy. Long‐term mortality was higher in patients with malignancy (P<0.001), while short‐term outcome was comparable (P=0.17). In a subanalysis, long‐term mortality was comparable between TTS patients with malignancies and ACS patients with malignancies (P=0.13). Malignancy emerged as an independent predictor of long‐term mortality. Conclusions: A substantial number of TTS patients show an association with malignancy. History of malignancy might increase the risk for TTS, and therefore, appropriate screening for malignancy should be considered in these patients. Clinical Trial Registration: URL: http://www.clinicaltrial.gov. Unique identifier: NCT01947621.
Gesehen am 14.10.2019